Improving business environments: a new approach to promote trade openness?. Issue 1 (2nd January 2023) - Cui, Xinsheng; Guo, Longfei; Bian, Yuanyue
ABSTRACT: Improving business environments as a kind of internally oriented institutional reform has been approved to attract Foreign Direct Investment and promote foreign trade. However, its effect on trade openness has been ignored. By introducing a dummy variable of the border into the gravity equation model, this study redefines and measures the trade openness, representing the ease of goods and service import of an economy. Then we estimate the impact of business environments on trade openness with the ease of doing business score of the World Bank's Doing Business project. The results reveal that, although some countries tend to implement trade protectionism in the time of economic crises and the trade openness suffers temporary setbacks, the overall development trend of the world economy increasingly opens up. Besides, the level of trade openness varies significantly among economies where developed countries demonstrate more openness than developing ones. More importantly, we find the positive effect of business environments on trade openness and the countries with lower development level benefited more from the improving business environments. It highlights the importance of improving business environments in promoting trade openness in the developing world.